2018
DOI: 10.1039/c8cc07339b
|View full text |Cite
|
Sign up to set email alerts
|

A single but hydrogen-bonded water molecule confined in an anisotropic subnanospace

Abstract: A single but H-bonded H2O was realized within an anisotropic subnanospace using an open-cage C60 derivative having hydroxy groups on the opening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 34 publications
2
39
0
Order By: Relevance
“…Communications 320 K. To avoid the dimerization of NO@3, the sample concentration was set to 1.0 mM in which the NO@3/ (NO@3) 2 ratio is predicted to be 98:2 from the association constant. [13] The chemical shifts of diamagnetic 3 were temperature-independent at this concentration ( Figure S5). As shown in Figure 4 a, the methine protons highlighted with red, green, and blue showed large paramagnetic shifts at 260 K when compared with those in a reference (3).…”
Section: Angewandte Chemiementioning
confidence: 94%
“…Communications 320 K. To avoid the dimerization of NO@3, the sample concentration was set to 1.0 mM in which the NO@3/ (NO@3) 2 ratio is predicted to be 98:2 from the association constant. [13] The chemical shifts of diamagnetic 3 were temperature-independent at this concentration ( Figure S5). As shown in Figure 4 a, the methine protons highlighted with red, green, and blue showed large paramagnetic shifts at 260 K when compared with those in a reference (3).…”
Section: Angewandte Chemiementioning
confidence: 94%
“…At this concentration, a monomer/dimer ratio is expected to be 77:23. [13] Considering the association constant and composition ratio, the H 2 Oadsorbed species are constituted of H 2 O@3, (H 2 O@3) 2 , (H 2 O@3)•(3), and (H 2 O@3)•(NO@3) with a ratio of 14:5:35:46 as being in a state of dynamic equilibrium.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The notation indicates the modified exit ridge. NO@C60-OH1 (Hasegawa et al, 2018a) and NO@C60-OH3 were prepared by following the literature (Hasegawa et al, 2018a) and the modified procedures are described in references (Hasegawa et al, 2018a;Hashikawa et al, 2018)]. DFT optimized structures of a) NO@C60-OH1, and b) NO@C60-OH3.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In a series of recent publications, the Kyoto group has shown that it is possible to encapsulate small and even reactive molecules in a modified C 60 cage with tailored entrance and exit holes (Hasegawa et al, 2018a;Futagoishi et al, 2017;Hashikawa et al, 2018). Using such designer type open cages instead of closed structures creates a new route for the preparation of interesting compounds.…”
Section: Introductionmentioning
confidence: 99%